MEMPERKUAT PERAN SUKUK NEGARA DALAM PEMBANGUNAN EKONOMI INDONESIA - Beik, Irfan Syauqi (Al-Infaq: Jurnal Ekonomi Islam, 2011)
Sukuk is one of the Islamic financial instruments which grows up very rapidly for the last two decades. Globally sukuk issuance has reached USD 199.18 billion as of December 2010. It is expected to increase over time. Indonesia being the most populous Muslim country in the world should play more active role in utilizing sukuk as its developmental instrument. This paper attempts to discuss the importance of using sukuk, especially sovereign sukuk known as SBSN (Surat Berharga Syariah Negara), in the development of Indonesia’s economy. In order to have bigger multiplier effect towards the economy, sovereign sukuk issuance must be focused on three major orientation, i.e. infrastructure development, labor intensive sectors and optimization of local potential. Hence, better regulation support and innovative sukuk product are highly needed.